Brown rice as a potential feedstuff for poultry - Mustapha, Nurul Asyifah; Abd. Aziz, Suraini; Phang, Lai Yee; Mohd Nadzri, Azlian (Oxford University Press, 2012)
Rice, especially brown rice, has the potential to replace corn as a feedstuff for poultry. It is an inexpensive local feed source with high availability and low production and processing costs. Two local varieties of brown rice, MR239 and MR257, were investigated for use as feedstuffs in the poultry industry, including their composition and TME values (using the force-feeding technique). The MR239 and MR257 varieties of brown rice contained nutrients such as CP, fat, ash, and carbohydrates. The energy content and amino acid profile of MR239 and MR257 are reported. The nonstarch polysaccharides in MR239 and MR257 consisted of CF, NDF, ADF, and acid detergent lignin. The β-glucan and arabinoxylan contents in MR239 and MR257 were determined. Both varieties of brown rice were found to be potential sources of feed for poultry.